Star formation history of irregular galaxies - Hatzidimitriou, Despina (1997)
Irregular galaxies are generally less massive and less evolved systems than spirals. They constitute a different sort of system in which to study the processes of star formation and galactic evolution. The star formation history of Irregular Galaxies may be affected by several different factors. However, detailed knowledge of the star-formation history of a significant number of objects is necessary before it becomes possible to determine which parameters are important. In the last few years, there has been significant progress on this front. For the first time, we begin to probe in some detail the star-formation history of a fair number of resolved Irregulars in the Local Group. In the present, these results are summarized.
Keywords: 98.56.Si; 98.56.Wm; 98.62.Ai; 98.62.Lv; 98.62.Qz; Dwarf galaxies; luminosities; Magellanic Clouds and other irregular galaxies; Magnitudes and colors; morphology and overall structure; Origin formation evolution age and star formation; radii; Stellar content and populations